Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018 IEEE 19th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC) 2018
DOI: 10.1109/spawc.2018.8445936
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Edge Computing for Cellular-Connected UAV: Computation Offloading and Trajectory Optimization

Abstract: This paper studies a new mobile edge computing (MEC) setup where an unmanned aerial vehicle (UAV) is served by cellular ground base stations (GBSs) for computation offloading. The UAV flies between a give pair of initial and final locations, during which it needs to accomplish certain computation tasks by offloading them to some selected GBSs along its trajectory for parallel execution. Under this setup, we aim to minimize the UAV's mission completion time by optimizing its trajectory jointly with the computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 13 publications
(32 reference statements)
0
98
0
Order By: Relevance
“…On the other hand, in practice, small UAVs may also have the need to offload the computation tasks to ground BSs in cellular-connected UAVs. By exploiting its LoS dominant links with many ground BSs, a UAV user can simultaneously connect with multiple GBSs to exploit their distributed computing resources to improve the computation offloading performance [150]. In [150], it has been shown that when the number of task-input bits is sufficiently large, the UAV should hover above its associated GBSs in order to achieve the most efficient computation offloading.…”
Section: Mobile Edge Computingmentioning
confidence: 99%
“…On the other hand, in practice, small UAVs may also have the need to offload the computation tasks to ground BSs in cellular-connected UAVs. By exploiting its LoS dominant links with many ground BSs, a UAV user can simultaneously connect with multiple GBSs to exploit their distributed computing resources to improve the computation offloading performance [150]. In [150], it has been shown that when the number of task-input bits is sufficiently large, the UAV should hover above its associated GBSs in order to achieve the most efficient computation offloading.…”
Section: Mobile Edge Computingmentioning
confidence: 99%
“…A. Obtaining g (λ, µ, ν, ω, η) by Solving Problem (25) For any given value of (λ, µ, ν, ω, η) in the feasible set of problem (D2), the dual function can be obtained by solving problem (25). Note the problem (25) can be decomposed into KN independent subproblems, and each one is further decomposed into several subproblems as follows.…”
Section: Energy Minimization With Fixed Trajectorymentioning
confidence: 99%
“…The role of the UAV Operation modes Contributions [3] User with computation task Partial offloading Cost minimization [4] User with computation task Partial offloading Cost minimization [5] User with computation task Partial offloading Completion time minimization [6] MEC server executing computation Partial offloading Architecture establishment [7] MEC server executing computation Partial offloading Energy consumption minimization [8] MEC server executing computation Partial offloading Energy consumption minimization [9] MEC server executing computation Partial offloading and binary computation Computation bits maximization [10] Relay offloading computation task Partial offloading Offloading bits maximization are assumed to hover in the sky and their trajectories are not optimized. Different from the works in [3] and [4], the authors in [5] proposed a resource allocation strategy that jointly optimizes the trajectory of the UAV and the offloading time in order to minimize the mission completion time of the UAV.…”
Section: Referencementioning
confidence: 99%